Immunological profiles of immune restoration disease presenting as mycobacterial lymphadenitis and cryptococcal meningitis - Tan, D.; Yong, Y.; Tan, H.; Kamarulzaman, A.; Tan, L.; Lim, A.; James, I.; French, M.; Price, P. (2008)
Objectives A proportion of HIV patients beginning antiretroviral therapy (ART) develop immune restoration disease (IRD). Immunological characteristics of IRD were investigated in a cohort of HIV patients beginning therapy in Kuala Lumpur, Malaysia. Methods Peripheral blood mononuclear cells were collected at weeks 0, 6, 12, 24 and 48 of ART from five patients experiencing IRD two with cryptococcal and three with Mycobacterium tuberculosis (Mtb) disease, eight non-IRD controls who had begun ART with CD4 T-cell counts of < 100 cells/mu L and 17 healthy controls. Leukocytes producing interferon-gamma (IFN gamma) were quantified by enzyme-linked immunospot assay after stimulation with purified protein derivative (PPD), early secretory antigenic target-6 (ESAT-6), Cryptococcus neoformans or Cytomegalovirus antigens. Plasma immunoglobulin (IgG) antibodies reactive with these antigens were assessed by enzyme-linked immunosorbent assay. Proportions of activated (HLA-DRhi) and regulatory (CD25 CD127(lo) and CTLA-4(+)) CD4 T-cells were quantified by flow cytometry. Results Plasma HIV RNA declined and CD4 T-cell counts rose within 8-27 weeks on ART. Mtb IRD patients displayed elevated IFN gamma responses and/or plasma IgG to PPD, but none responded to ESAT-6. Cryptococcal IRD occurred in patients with low baseline CD4 T-cell counts and involved clear IFN gamma and antibody responses to cryptococcal antigen. Proportions of activated and regulatory CD4 T-cells declined on ART, but remained higher in patients than in healthy controls. At the time of IRD, proportions of activated CD4 T-cells and regulatory CD4 T-cells were generally elevated relative to other patients. Conclusions Cryptococcal and Mtb IRD generally coincide with peaks in the proportion of activated T-cells, pathogen-specific IFN gamma responses and reactive plasma IgG. IRD does not reflect a paucity of regulatory CD4 T-cells.